Ragam Aktivitas Urease dan Fosfomonoesterase serta Perannya dalam Ketersediaan Nutrisi N dan P pada Tanah Kebun Biologi Wamena - Rahmansyah, Maman; Latupapua, H.J.D.; Sudiana, I Made (JURNAL BIOLOGI INDONESIA, 2002)
ABSTRACTDiscrepancy of urease and phosphomonoesterase activities and its role in establishing Nand P nutrition in soil collected from Wamena Biological Research Station. Microbialactivities in soil lead to know for establishing soil nutrient status. Accordingly, soil collectedfrom Biological Research Station in Wamena then sent to the laboratory and determined on itsenzymatic activities and the physicochemical, as well. In this work, the enzymatic activities ofurease and phosphomonoesterase were examined in relation with soil microbial respiration, inorder to understand the mineralization of nitrogenous and phosphorus compound in soil. Soilrespiration rate (2.43-3.21 mg C02 g-dm12hour) designated variation in each sample, as wellas urease (8.6-23.5 unit/g soil) and phosphomonoesterase (5.5-7.9 unit/g soil) activities.Phosphomonoesterase activity showed strong correlation with respiration rate within soil; andreveal to the configuration of the bioactivities and physicochemical soil figures concluded thatthe B sample has the poor fertility. The phenomenon of data fulfill that bioactivities hadcorrelation with the physicochemical compound in the soil.Keywords: respiration, urease, phosphomonoesterase, Wamena Biological Research Station.